Experimental study of ultrasonic atomizer effects on values of EC and pH of nutrient solution - lakhiar, Imran Ali; Liu, Xingda; Wang, Guanqun; Gao, Jianmin (International Journal of Agricultural and Biological Engineering, 2018)
The objectives of this research were to reveal how main working parameters of ultrasonic atomizers would influence key properties of the atomized nutrient solution in an aeroponics system. The Yamazaki tomato nutrient solution was selected as a nutrient example. Uniform design (UD) method U12 (122×13) was adopted to arrange the test. In this test, spraying time and interval time were taken as quantitative factors with 12 levels (10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, and 120 min, respectively), and ultrasonic atomizer frequency was taken as qualitative factor with 3 conditions (28 kHz, 107 kHz, 1.7 MHz). Based on test data, two regression formulations used to predict the values of ΔEC, and ΔpH of atomized Yamazaki tomato nutrient solution was established and inspected. The spraying interval time of ultrasonic atomizers had no significant effect on EC and pH of the atomized Yamazaki tomato nutrient solution; the ultrasonic atomizer frequency was more effective than spraying time on the values of EC and pH; the values of EC and pH became maximum at (f3, T1) = (1.7 MHz, 120 min) and minimum at (f1, T1) = (28 kHz, 10 min). It was concluded that the effect of high-frequency (1.7 MHz) ultrasonic atomizer on EC and pH of the Yamazaki tomato nutrient solution was beyond the standard value for tomato growth. Therefore, the high-frequency (1.7 MHz) ultrasonic atomizer is not suitable for aeroponics cultivation when using the Yamazaki tomato nutrient solution as aeroponics nutrient solution.Keywords: aeroponics, tomato nutrient solution, EC, pH, ultrasonic atomizer frequency, spray time, interval time, uniform designDOI: 10.25165/j.ijabe.20181105.3790Citation: Lakhiar I A, Liu X D, Wang G Q, Gao J M. Experiment study of ultrasonic atomizer effects on values of EC and pH of nutrient solution. Int J Agric & Biol Eng, 2018; 11(5): 59–64.